Workshop on Soil Fertility Research for Bean Cropping Systems in Africa (1988, Addis Ababa, Ethiopia). Proceedings - Wortmann, Charles S. (Southern Africa Development Coordination Conference (SADCC), 1988)
A regional workshop was held in Ethiopia (Eastern Africa) to assess the status, future needs, and methodological issues of soil fertility research for bean cropping systems on the continent. Traditional forms of soil fertility maintenance, diagnosis of soil fertility constraints, nutrient requirements, use of fertilizers, cropping systems and soil fertility, and soil organic matter and the use of green manures and mulching were addressed. Country reports were given on the research experience with inorganic and organic fertilizers in the southern highlands of Tanzania, the nature and importance of soil-related constraints to bean production in Kenya, and the relationship between soils and bean production in Angola. Fertilizer requirements for dry bean production in Kenya were also reviewed. Recommendations for the national agricultural research systems and for CIAT regarding future research approaches are included. (CIAT)